Cultivating the Spirit of Entrepreneurship in Students Through Project Market Day: An Approach to Strengthening Character Values - Kuswanto, Kuswanto; Hakam, Kama Abdul; Nurihsan, Juntika; Rakhmat, Cece; Silawati, Endah; Salamah, Ilma Siti (EduBasic Journal: Jurnal Pendidikan Dasar, 2025)
Entrepreneurship education is a field of study that provides space for students to develop their creativity. Through market day activities, students can learn directly about the market situation and recognize the business world. However, there is a gap in the literature regarding how entrepreneurship activities should be implemented in primary schools. This study aims to examine and analyze the entrepreneurial spirit of students from the results of market day activities, how it impacts students, and how character values are internalized. The approach in this research is descriptive qualitative. The subjects recruited in this study were principals, teachers, and students. Collection techniques and tools were through observation, interviews, and documentation. The results revealed that students displayed positive character values starting from planning and preparing and continuing until market day activities. In conclusion, market day activities have proven to be an effective program for cultivating the entrepreneurial spirit of students. It can be seen that the purpose of the market day is not only to improve entrepreneurial skills but also to become a means of learning character values that are important for students' lives in the future. This research can be a reference for educators in creating innovative learning and being able to internalize character values through market day projects.